Efficiency and preference for alternative activities during schedule thinning with functional communication training. Issue 1 (24th October 2021) - Simmons, Christina A.; Salvatore, Giovanna L.; Zangrillo, Amanda N.
Abstract : Functional communication training is an effective treatment for decreasing socially reinforced destructive behavior (Carr & Durand, 1985). Clinicians frequently use multiple schedules to thin the reinforcement schedule (Hanley et al., 2001). Individuals are often taught to wait for functional reinforcers without alternative programmed stimuli. However, concurrently available items and activities are often accessible in the natural environment. In this study, we taught 4 participants a functional communication response to access functional reinforcers. We implemented a multiple schedule during schedule thinning, comparing a control condition (nothing available during S Δ intervals) to separate conditions with items/activities (moderately preferred tangible items, attention, demands) noncontingently available during S Δ intervals. After reaching the terminal schedule in one condition, therapists assessed participant preference across S Δ conditions. For all participants, the terminal schedule was reached with alternative items and activities, and participant preference corresponded with the most efficient schedule thinning condition. Therapists also indicated preference for alternative items/activities.